Faktor Penyebab Perundungan Pada Pelajar Usia Remaja Di Pangandaran - Alfiyatun; Anna Vanista; Imas Patmawati (Jurnal Pendidikan Sosial Dan Konseling, 2023)
Bullying is an act of using power to bring any harm into a person or some people who is either verbally, physically, and psychologically victimized, traumatized, and helpless (Sejiwa, 2008). Teens who are intended to be the victims of bullying are at greater risk of health problems, both physically and mentally. As for problems more likely to be suffered by the victims of intimidation, include various mental problems such as depression, anxiety and sleep problems that may be carried into adulthood, physical health pathologies, such as headaches, abdominal pain and muscle load, and decreasing spirit of learning and academic achievement. In certain cases, victims of bullying may show violent characteristics. As happened to a 15 years old teenager in Denpasar, Bali, who killed his own friend for a revenge to the victim. Perpetrators claim to often be the target of bullying since the first grade of junior high school.This article is intended to find out the causes of bullying by teenagers, roles in bullying, and types of bullying. The data source of this paper is done by documentation study method. In this article the results of factors that affect the occurrence of bullying come from individuals, families, play groups, to the community of perpetrators. This action is closely related to the world of social work, which they should be activate their role as a conselor for cutting the bully behavior off.